Tumor-specific silencing of COPZ2 gene encoding coatomer protein complex subunit zeta2 renders tumor cells dependent on its paralogous gene COPZ1 - Shtutman, Michael; Baig, Mirza; Levina, Elina; Hurteau, Gregory; Lim, Chang-uk; Broude, Eugenia; Nikiforov, Mikhail; Harkins, Timothy T.; Carmack, C. Steven; Ding, Ye; Wieland, Felix T.; Buttyan, Ralph; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Anticancer drugs are effective against tumors that depend on the molecular target of the drug. Known targets of cytotoxic anticancer drugs are involved in cell proliferation; drugs acting on such targets are ineffective against nonproliferating tumor cells, survival of which leads to eventual therapy failure. Function-based genomic screening identified the coatomer protein complex ζ1 (COPZ1) gene as essential for different tumor cell types but not for normal cells. COPZ1 encodes a subunit of coatomer protein complex 1 (COPI) involved in intracellular traffic and autophagy. The knockdown of COPZ1, but not of COPZ2 encoding isoform coatomer protein complex ζ2, caused Golgi apparatus collapse, blocked autophagy, and induced apoptosis in both proliferating and nondividing tumor cells. In contrast, inhibition of normal cell growth required simultaneous knockdown of both COPZ1 and COPZ2. COPZ2 (but not COPZ1) was down-regulated in the majority of tumor cell lines and in clinical samples of different cancer types. Reexpression of COPZ2 protected tumor cells from killing by COPZ1 knockdown, indicating that tumor cell dependence on COPZ1 is the result of COPZ2 silencing. COPZ2 displays no tumor-suppressive activities, but it harbors microRNA 152, which is silenced in tumor cells concurrently with COPZ2 and acts as a tumor suppressor in vitro and in vivo. Silencing of microRNA 152 in different cancers and the ensuing down-regulation of its host gene COPZ2 offer a therapeutic opportunity for proliferation-independent selective killing of tumor cells by COPZ1-targeting agents.